Therapeutic Potential of Targeting Periostin in the Treatment of Graves’ Orbitopathy - Jang, Sun Young; Kim, Jinjoo; Park, Jung Tak; Liu, Catherine Y.; Korn, Bobby S.; Kikkawa, Don O.; Lee, Eun Jig; Yoon, Jin Sook (Frontiers in Endocrinology, 2022)
Periostin is a matricellular protein that is ubiquitously expressed in normal human tissues and is involved in chronic inflammatory and fibrotic disease. POSTN (gene encoding periostin) expression in Graves’ orbital tissues and healthy control tissues was studied, and the role of periostin in Graves’ orbitopathy (GO) pathologic mechanism was examined through small-interfering RNA (siRNA)-mediated silencing. POSTN gene expression was significantly higher in Graves’ orbital tissues than healthy control tissues in real-time PCR results and immunohistochemical staining. Silencing periostin significantly attenuated TGF--induced profibrotic protein production and phosphorylated p38 and SMAD protein production. Knockdown of periostin inhibited interleukin-1-induced proinflammatory cytokines production and phosphorylation of NF-κB and Akt signaling protein. Adipogenesis was suppressed in periostin-targeting siRNA transfected GO cells. Periostin might contribute to the pathogenic process of inflammation, fibrosis and adipogenesis of GO. Our study provides in vitro evidence that periostin may be a novel potential therapeutic target for the treatment of GO.